Biological and prognostic differences between symptomatic colorectal carcinomas and those detected by screening. Issue 10 (October 2019) - Téllez, Teresa; Abitei, Cristina; Padilla-Ruiz, María del Carmen; Rivas-Ruiz, Francisco; Fúnez, Rafael; Pereda, Teresa; Rodrigo, Isabel; Alcaide, Julia; Baré, María Luisa; Morales Suárez-Varela, María Manuela; Zabalza, Iñaki; Sánchez del Charco, Matilde; et al.
Abstract: Introduction: Few studies have been conducted to establish the relationship between colorectal cancer screening programmes and survival adjusting by stage and, to determine whether there are differences, at a biological level, between the tumours of asymptomatic and symptomatic patients. Accordingly, the aim of this study is to evaluate clinical, biological and survival differences between symptomatic colorectal tumours and those detected by screening. Study method: A prospective cohort study was performed of patients subjected to surgical intervention during the period 2010–2012, at different hospitals in Spain. In every case, clinical, pathological, biological and survival-related variables were obtained. Results: A total of 2634 patients from the CARESS-CCR cohort were analysed; of these, 220 were diagnosed through screening. The asymptomatic patients were younger, had a higher Body Mass Index (BMI), a lower degree of perineural invasion and a less advanced T stage and nodular stage, and the tumour was frequently located on the right side of the colon. All of these differences were statistically significant. The serum tumour marker carbohydrate antigen 19.9 (CA 19.9) was found more frequently in the symptomatic patients (p < 0.05). However, no significant differences were found regarding the markers of tumour biology: Ki67 (proliferation), CD105 (angiogenesis) and the Terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) assay (apoptosis). The patients with asymptomatic tumours had a lower mortality at five years than those diagnosed presenting symptoms. Conclusions: The detection method employed influenced the survival of patients with colorectal cancer and there were no significant biological differences between the study groups.